Analysis of solar cells can be used in the design of solar-powered UAV (Вестник транспорта - Transport xabarnomasi, 2025)
Interest in solar-powered unmanned aerial vehicles (UAV) is increasing today due to their ability to fly for long periods of time. Solar cells play an important role in their long-term flight, and the right choice of solar cell technology has a significant impact on the performance and efficiency of these solar-powered UAVs. This article analyses various solar cells for solar powered UAVs, considering their specifications such as efficiency, power output, weight, etc., and other factors such as installation, durability, and cost effectiveness. Various types of solar cells, including silicon-based, thin-film, multi-junction, and emerging technologies, are evaluated based on their suitability for solar-powered UAV applications and at the end, conclusions are presented on the selection of the most optimal solar cell that can be used in the design of such UAVs.